A presença de estudantes cotistas negros na Universidade Estadual de Londrina : dez anos do sistema de cotas raciais (2005-2014) - Cesário, Kely Moreira (2016)
Since 2004, various public institutions of higher education throughout the country adopted the policy of social and racial quotas as a guarantee admission to a sector of society where the poor people has little access to public universities. The State University of Londrina (UEL), quota policy began in the vestibular 2005, being re-evaluated in 2012, when the issue of proportionality has been changed, in which the reserve for racial quota holders became the number of vacancies offered per course. A new evaluation and approval for the continuation of this policy will be discussed in 2017. This work proposes to make a quantitative and qualitative data analysis from the racial quota system at UEL, over a period of ten years (2005- 2014) in order to understand and analyze the performance of racial quota students in 69 undergraduate courses offered by UEL and identifying the main problems faced by them in graduation, how they deal or overcome such problems, how they are after finishing the course and how they evaluate the quota system. Quantitative analysis was based on information provided by the Dean of Undergraduate Studies through a spreadsheet containing data of enrolled students, graduates and dropouts in the three entry systems (universal, racial quotas and public school quotas) from 2005 to 2014. For the qualitative data were provided a questionnaire with open and closed questions for two groups of students, active in undergraduate and alumni. The study aligns the sociologists' thinking of Bourdieu and Lahire, about habitus, and the provisions and strategies used by racial quota holders to stay on a college field where historically had no representation to be seen as socially unfit.